Positioning - Fleischer, Daniel; Pich, Christian (Algorithms for Sensor and Ad Hoc Networks, 2007)
Many applications of sensor and ad hoc networks profit from the knowledge of geographic positions of all or just some of the sensor nodes. E.g., geometric routing can use positional information to pass packets efficiently to target nodes. Tasks like measuring temperature or humidity levels of a certain area can only be fulfilled, if each sensor node knows its geographic position or at least an approximation of it. Attaching a GPS (global positioning system) to each sensor node is an undesirable solution, since GPS is quite costly and clumsy, compared to the small sensor nodes. Furthermore, the perception of GPS signals might be disturbed when there is no direct connection to the satellites due to some obstacles (buildings, trees, ...).